Assessing the profitability of glutinous rice production in the Philippines - Beltran, Jesusa C.; Ante, Ralph Homer L.; Arida, Imelda A.; Manalili, Rowena G.; Daplin, Kristine Marie A.; Relado-Sevilla, Rhemilyn Z.; Moya, Piedad; Romero, Marissa V.; De Leon, Teresa Joi P.; Chua, James D.; Baltazar, Marco Antonio; Valencia, Maria Shiela D.; et al. (Crop Science Society of the Philippines, 2025)
Rice trade liberalization has negatively affected the income of Filipino rice farmers, and this could provoke them into reducing their rice cultivation. Production of glutinous rice, which has progressing demand at local and international levels, could be an alternative for farmers to keep their rice farming enterprise viable. However, there have been very few interventions to increase its yield level and local production. This could be linked with the limited information and data about its production dynamics, marketing, and full potential. Hence, this paper assessed the potentials and profitability of glutinous rice production in the Philippines. A total of 93 farmers were selected through multi-stage random sampling and interviewed in the provinces of Camarines Sur, Iloilo, and Abra. Descriptive statistics and costs and returns were used for data analysis. Results showed that local glutinous rice production is profitable with positive net returns in all sites. Return on investment ranges from 15 to 29%. Findings pointed out that the current local glutinous rice industry has a high potential for expansion and opportunity for import substitution. Strategies for yield enhancement, production cost reduction, and premium quality preservation are recommended.